KRITIK SOSIAL DALAM NOVEL MELANGKAH KARYA JOMBANG SANTANI KHAIREN (KAJIAN SOSIOLOGI SASTRA ALAN SWINGEWOOD) - Milayanti Milayanti; Mahatir Musaa,d; Risma Alam (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms of social criticism reflected by the author through his novel. The researcher uses Alan Swingewood's theory of literary sociology in viewing the social criticism that J.S Khairen wants to convey in the novel Melangkah. This study uses a qualitative method, with a type of library research. The results of the study indicate the existence of a form of social criticism by the author towards the gaps felt by most Indonesian people, especially Sumba Island. The form of gap experienced and highlighted by the author in this novel is the uneven development of infrastructure that can support the economy of the Sumba community. The forms of infrastructure inequality are inadequate electricity, transportation facilities, internet access, lack of clean water availability, inadequate road access and in terms of environmental cleanliness.